PENINGKATAN HASIL BELAJAR MATERI OTONOMI DAERAH DALAM PELAJARAN PPKn METODE RESITASI - Sumarwoto Sumarwoto (LPPM UNISDA, 2020)
Learning PPKn in class IX-B SMP Negeri 1 Pule Trenggalek has serious problems. In daily tests on regional autonomy, the average score is very low, namely 56.6. Students who have achieved mastery learning are 17 students or 51.5%. There are 16 students who have not reached the completeness of learning or 48.5%. The most mistakes made by students when describing the principles of regional autonomy, describing central government affairs, describing regional government affairs, examining regional autonomy implementers, describing the duties and powers of regional heads, describing the duties, functions and powers of DPRD, describing the importance of community participation in formulating public policies as well as looking for a relationship between the implementation of regional autonomy and the development carried out in their respective regions. Based on the results of discussions with colleagues, it was revealed that the learning that had been taking place did not involve the students maximally. In the teaching and learning process of PPKn, teachers do not provide much time for students to be involved in learning and discovery of learning concepts. Based on the above, it is necessary to conduct an action research by applying recitation. In this study, researchers used a classroom action research model. Observation / observation is divided into two learning cycles, each cycle carried out 2 meetings. Two cycles were made to improve the learning system being implemented. Based on the description of the discussion above, it is concluded that the application of the recitation method to regional autonomy in PPKn lessons begins by giving students assignments to make summaries of the articles contained in the clippings. In the next lesson each group gets an assignment to conduct a discussion. This is intended to increase student involvement in learning. The application of the recitation method can improve student learning outcomes on regional autonomy material in PPKn lessons.